Challenges in the management of groundwater in the municipality of Sete Lagoas - MG (Research, Society and Development, 2023)
The municipality of Sete Lagoas, in the State of Minas Gerais, faces several challenges for the management of water resources, mainly due to the advance of urbanization on a complex and unstable geological structure. Much of the municipality is characterized by carbonate rocks, highly susceptible to dissolution processes in aqueous media. The local geology, added to certain anthropic activities, configure a critical scenario in several aspects, among which the loss of water quality, formation of cavities and instability of extensive areas, with a high risk of subsidence, stand out. The geological and hydrogeological configuration of the municipality induced the institution of a special standardized procedure by the managing body of state waters in Minas Gerais to discipline the processes for granting the right to use groundwater in the municipality of Sete Lagoas. Soil and surface water contamination factors increase the risk of compromising the quality of groundwater, given the conditions of water connection with groundwater levels from fractures, faults, sinks and other conduits. The object of this article is the analysis of the challenges for water management in the municipality, considering the need to guarantee access to this natural resource in quantity and quality for current and future uses, and the risk of soil collapses in urban areas in due to local geology added to anthropic actions.